A CASE SERIES AND LITERATURE REVIEW: MANAGEMENT STRATEGIES FOR RADIATION-INDUCED ULCERS OF THE CHEST - Kristine, Elizabeth; Syed Faqeer Hussain Bokhari; Sweety Pribadi (Universitas Airlangga, 2024)
Highlights: Radiotherapy leads to a high occurrence of skin alterations and can advance to different levels of tissue damage, presenting challenges in treatment. Management can be effective employing diverse wound treatment methods, although severe cases may necessitate surgical intervention. Surgery takes into several key considerations to increase chances of success and tackle specific issues of chest wall instability and breast reconstruction. Abstract: Introduction: Radiotherapy as an adjunct to cancer treatment causes a high incidence of radiation-induced tissue injury, ranging from radiation dermatitis to severe osteoradionecrosis. Currently, no gold standard exists in the management of radiation injury. Various strategies ranging from modern wound treatment to surgical management have been studied. Case Illustration: Three women presented with varying degrees of ulceration in the chest during or shortly following radiotherapy. Each case followed different approaches to management. One case solely received wound treatment, another received wound treatment and a sequestrectomy, and the third required surgical reconstruction of the chest wall and defect. Discussion: Methods of wound treatment range from topical agents, barrier films and dressings, hydrogel and hydrocolloid dressings, miscellaneous treatments, and biodressings. Surgery is required in severe cases, particularly with osteoradionecrosis. This may include wound debridement, biopsy, chest wall stabilization, closure using various flaps, and potential breast reconstruction. Conclusion: Radiation-induced ulcers of the chest pose a complex issue. Understanding effective treatment methods and key surgical principles is important for ensuring better outcomes. Further studies are needed to provide a complete guide to treatment.